Problem-Based Learning Implementation to Enhance Sixth-Grade Students' Science Learning Outcomes: An Action Research Study - Reni Atika; Azizah Azizah; Nuraini Nuraini; Zulnuraini Zulnuraini; Dyah Aini Purbarani (Papanda Publisher, 2026)
Low IPAS learning outcomes among sixth-grade students at Alkhairaat Tondo Elementary School, attributed to conventional teacher-centered instruction, necessitated pedagogical intervention to enhance student achievement and engagement. This study aimed to improve IPAS learning outcomes through systematic implementation of the Problem-Based Learning (PBL) model. Employing classroom action research based on the Kemmis and McTaggart model, this study was conducted across two cycles with 26 sixth-grade students during October-November 2025. Data were collected through criterion-referenced achievement tests (20 items, KR-20 = 0.82) and validated observation sheets (Cohen's kappa = 0.85) documenting teacher and student activities. Analysis utilized both quantitative descriptive statistics and qualitative rubric-based assessment. Classical completeness increased significantly from 58% in Cycle I to 88% in Cycle II, representing a 30 percentage point improvement. Concurrently, teacher activity performance improved from 66% (adequate) to 91% (very good), while student engagement advanced from 64% to 89%. Notably, mid-range achievers (initial scores 60-75) demonstrated greater gains (average 18 points) compared to lower-achieving students (average 12 points), suggesting differential PBL impact across performance levels. Systematic PBL implementation effectively improves IPAS learning outcomes while enhancing teacher facilitation quality and student engagement. The iterative action research process enabled progressive refinement of instructional practices, though lower-achieving students may require additional scaffolding for equitable outcomes.